KAJIAN TEKNIK BUDIDAYA TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) PETANI SWADAYA KECAMATAN LUBUK DALAM KABUPATEN SIAK PROVINSI RIAU - Sihombing, Darwin; Puspita, Fifi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The objective of this research was to study of cultivation techniques palm oil independent farmers and social aspects to palm oil production. This research has conducted in Lubuk Dalam District Siak Regency from August 2014 until October 2014. The research was conducted using survey and the sampling used for this research purposive sampling. Consist of 60 sample, based on 10% level of representation. 30 sample drawn from Rawangkao Village and 30 sample drawn from Lubuk Dalam Village. The parameters studied were, land clearing, the origin of the seeds, size of planting holes, seed age, plant spacing, pruning, control of weeds and fertilization. The results show that the average production palm oil of farmers are still very low at less than 50% when compared to the average production of palm oil of PPKS Medan on mineral lands in general. The low production of palm oil cultivation techniques of farmers due to conducted as seed origin, plant spacing, pattern spacing, the size of the planting hole, transplanting seedlings into the ground, fertilizing, are still quite low level of the appropriate palm oil cultivation techniques application in the field. Â Keywords: Cultivation Techniques Palm, Independent Farmers, Siak Regency Â